Street Children's Rights in Poland - Kamila Zdanowicz-Kucharczyk; Izabela Seredocha (University of Lower Silesia, 2016)
The main objective of this paper is to present Polish street children's situation in connection to their rights. It is based on a PhD project that ran from 2009 to 2012. The phenomenon of street children is increasing worldwide, necessitating new ways of working with and supporting these children. Increasingly, not only material help but also emotional support for children`s choices being put forward. Therefore it is very important to spread knowledge about street children`s life. Research results described in this paper could help educators work with street children. Their life is presented within the legal framework concerning the rights of children. This kind of look clarifies not only street children`s situation, but also possible ways to help them. The empirical material is based on a documentary method, which includes participant observation, group discussion and photo-reports which give to street children the possibility to document their lives. It brings researchers and educators close to children and help to meet their choices and lives.